Alleviation of aflatoxin B1-induced gut toxicity via probiotic intervention through modulation of gut proteomes and microbiota - Liew, Winnie Pui Pui (2021)
Aflatoxin (AF) is a pervasive, extremely toxic contaminant produced by Aspergillus sp. that demands further research to explain the mechanisms of toxicity. A better understanding of AF’s patterns of toxicity and food contamination helps to address the harmful impacts on nation's health and economy. Among AFs, aflatoxin B1 (AFB1) is the most toxic and has been studied extensively. Lactobacillus casei Shirota (Lcs) is a probiotic with potential AFB1-binding ability. There is limited study available on the binding efficiency and interactions between Lcs and AFB1. The toxicity of AFB1, particularly towards the gut is not well studied. Besides, the pathways involved in the alleviation of AFB1-induced toxicity by probiotics remained undiscovered. Therefore, this research investigated the mechanism of Lcs in alleviating toxicity induced by AFB1 in both in vitro and in vivo experiments. Three distinct Lcs cellular components: live cell, cell wall, and heat-treated cell were incubated with different levels (2, 4, 6, 8, and 10 μg/mL) of AFB1. The AFB1-binding efficiencies of the bacterial cell fractions were estimated using an adsorption isotherm. The interactions between Lcs and AFB1 were investigated using scanning electron microscopy (SEM). The AFB1-removal ability of Lcs was further evaluated using the rat model. Sprague Dawley rats (Male; n=40) were separated into five treatment groups (Control, AFB1 exposure, Charcoal+AFB1, Lcs+AFB1, and Lcs). The rats were subjected to 25 μg/kg body weight (b.w.) daily. Upon the end of the animal study (four weeks), the biological samples (blood serum, urine, feces, intestine, spleen, liver, and kidney) were collected. Serum AFB1 and urinary AFM1 were evaluated using enzyme-linked immunosorbent assay (ELISA). Meanwhile, histological examination was performed on the tissues via hematoxylin and eosin (H&E) staining. The feces samples were subjected to gut microbiota analysis using metagenomic sequencing. Besides, the AFB1 most affected site was subjected to proteomic analysis via liquid chromatography coupled with tandem mass spectrometry (LC/MS/MS). The Langmuir model demonstrated that live bacterial cell and cell wall fraction possessed the highest binding efficiencies at 14.32x1010 and 16.34x1010 respectively. Lcs cells incubated with AFB1 appeared in curve-shaped with irregular and rough surface under SEM. Meanwhile, the AFB1 biomarkers’ level in both blood serum and urine samples, has been significantly (p<0.05) decreased by Lcs to 42% and 6%, respectively. Inflammation and abnormal cell growth were observed in AFB1-exposed rats, mainly in the jejunal tissue. Such adverse effects were greatly alleviated by Lcs supplementation. Moreover, AFB1 significantly induced the overgrowth of potentially pathogenic bacteria (Prevotellaceae NK3831 group and Prevotella 9) and reduction of normal/ beneficial microbiota (Lactobacillus, Eubacterium coprostanoligenes group, and Ruminiclostridium 6). This research showed that Lcs intervention successfully normalized the gut microbiota altered by AFB1 significantly (p<0.05). Based on the gut proteomes analysis, several pathways related to cancer, inflammation, and ROS generation were induced by AFB1. The altered gut proteome were reduced upon Lcs intervention. This may explain the alleviation of gut damage such as abnormal cell growth and inflammation observed in the intestine tissues. A total of 24 pathways involved in the alleviation of AFB1-induced toxicity by probiotic were identified. Probiotic Lcs was capable of maintaining the composition of gut microbiota and offers protection towards the gut health status. Lcs has become a popular probiotic supplement and its health-promoting effect coupled with its AF-removal ability is remarkable as a novel dietary approach for management of aflatoxicosis and AFs exposure. Nevertheless, further studies to elucidate the efficiency of Lcs at different dosages of AFB1 are warranted.